Cancer-related proteins in serum are altered in workers occupationally exposed to polycyclic aromatic hydrocarbons: a cross-sectional study. (8th February 2019) - Alhamdow, Ayman; Tinnerberg, Håkan; Lindh, Christian; Albin, Maria; Broberg, Karin
Abstract: Exposure to some polycyclic aromatic hydrocarbons (PAH) increases the risk of cancer and is common particularly for workers in occupations such as chimney sweeping. In exposed workers, screening of early cancer-related markers provides important information to identify individuals at risk. Here, we aimed to elucidate the associations between PAH exposure and serum levels of cancer-related proteins in 118 chimney sweeps and 126 occupationally unexposed controls, all non-smoking males from Sweden. Monoydroxylated metabolites of pyrene, phenanthrene, benzo[a]pyrene and benzo[a]anthracene were measured in urine using liquid chromatography coupled to tandem mass spectrometry and 90 cancer-related proteins were measured in serum using a proximity extension assay. Linear regression analysis adjusted for age and body mass index, and false discovery rate (FDR) identified 17 serum proteins that were differentially expressed (16 upregulated and 1 downregulated) in chimney sweeps compared with controls (FDR < 0.05). Concentrations of the peptidase kallikrein 13 (KLK13) showed significant positive associations with urinary concentrations of the PAH metabolites 3-hydroxybenzo[a]pyrene (3-OH-BaP) [B, 95% confidence interval (CI): 0.042, 0.008–0.076] and 3-hydroxybenzo[a]anthracene (3-OH-BaA) (B, 95% CI: 0.068, 0.002–0.134). Moreover, dose–response relationships were observed between KLK13 and 3-OH-BaP (trend test P = 0.027) and 3-OH-BaA ( P = 0.035). Pathway and gene ontology analyses showed that cell movement, cell adhesion and cell migration were the predominant molecular functions associated with the top differentially expressed proteins. In conclusion, we found a number of putative cancer-related proteins differentially expressed in workers exposed to PAH. This warrants effective measure to reduce PAH exposure among workers as well as further investigation to confirm these findings.